Small Farmers’ Agricultural Practices and Adaptation Strategies to Perceived Soil Changes in the Lagoon of Venice, Italy - Tiziana Floridia; Julia Prakofjewa; Luigi Conte; Giulia Mattalia; Raivo Kalle; Renata Sõukand (Agriculture)
Farmers have a pivotal responsibility in soil conservation: they can either preserve or deplete it through their choices. The responsibility of agriculture increases when practised in delicate ecosystems, such as lagoonal ones. The Venetian Lagoon islands, which are increasingly subjected to natural and anthropic subsidence, occasional flooding events (acqua alta), and eustatic sea level rise, are constantly exposed to erosive processes that challenge farmers to play with their adaptive capability. This research was carried out on the islands of Sant’Erasmo and Vignole, the most representative of island agriculture in the Venetian Lagoon: they almost exclusively rely on agriculture, which is almost nil in the other islands. This empirical research aimed to explore farmers’ agricultural practices, perceptions of soil changes, and how they adapt to them. It was fundamental for this study that the field research involved direct human contact with farmers (through semi-structured interviews) for data collection and using qualitative methods for data analysis, integrating scientific and non-scientific forms of knowledge and actors. The final purpose was to demonstrate the sustainability (valued on the potential depletion or regeneration capability) of agricultural practices and adaptation strategies on a theoretical basis. Despite their polycultural landscape (maintained by low-input farming systems), escaped from the predominant landscape oversimplification, Sant’Erasmo and Vignole are also subjected to unsustainable agricultural practices, including heavy mechanisation and synthetic inputs. Coupled with natural soil salinity that is exacerbated by increasing drought periods, these practices can contribute to soil degradation and increased salinity. The reported adaptation strategies, such as zeroed, reduced, or more conscious use of machines, were guided by the need to reduce the negative impact of soil changes on productivity. Our research revealed some of them as sustainable and others as unsustainable (such as increasing irrigation to contrast soil salinity). Participatory action research is needed to support farmers in designing effective sustainable agricultural practices and adaptation strategies.